The Age of Revolution, 1957 - Churchill, Winston S. (History of the English-Speaking Peoples., 2013)
The third volume of the Prime Minister's history of Britain follows the nation's ascent as a world power and its response to the threat of Napoleon. In the "wilderness" years after Sir Winston Churchill unflinchingly guided his country through World War II, he turned his masterful hand to an exhaustive history of the country he loved above all else. And the world discovered that this brilliant military strategist was an equally brilliant storyteller. In 1953, the great man was awarded the Nobel Prize for Literature for "his mastery of historical and biographical description as well as for brilliant oratory in defending exalted human values." This third of four volumes explores Britain's rise to world leadership during the eighteenth-century Age of Revolution. With characteristic eloquence, Churchill recounts the plunging of the South Seas company stock, the Spanish and Austrian Successions, the Treaty of Utrecht, the Seven Years' War, and the American and French Revolutions. This sweeping history is a must-read for history buffs. "This history will endure; not only because Sir Winston has written it, but also because of its own inherent virtues-its narrative power, its fine judgment of war and politics, of soldiers and statesmen, and even more because it reflects a tradition of what Englishmen in the hey-day of their empire thought and felt about their country's past."--The Daily Telegraph.